Role of the Nuclear Technology for Regional Border Security - Darsono Darsono; Elin Nuraini; Saefurrochman Saefurrochman; Sutadi Sutadi (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2025)
The smuggling of explosives, narcotics, weapons, and hazardous chemicals, as well as the illicit trafficking of radioactive and nuclear materials across the national border have threaten the security of all States. Nuclear technology has been developed to face these problems. Current inspection system for parcel, luggage, vehicle, and cargo uses imaging techniques based on the penetrating radiation of hard X-rays and Gamma-rays. These system are used to prevent the smuggling activity. RPM (Radiation Portal Monitor) is used to detect radioactive and nuclear materials. This paper describes the RPM, the cargo inspection system based on the penetrating high energy photon and neutron, as well as the potential cargo inspection system based on neutron reaction with materials inside a container. The discussions are focused on the research and development of the PGFNA (Prompt Gamma Fast Neutron Analysis) with associate particle method in BRIN (National Research and Innovation Agency) to detect C, N, and O which are the main chemical element of a contraband material. A neutron of 14.1 MeV from a neutron generator accelerator was used to excite the nuclides of C, N, and O and their gamma rays were measured by nuclear instrument of alpha-gamma coincident.  The results of PGFNA experiments using the alpha-gamma coincidence technique at 100 ns timing range of TPHC and at a neutron flux of 106 n /cm2.s showed that the technique worked and it was able to reduce the background count although a big sample was needed.